The effects of self-talk types and task complexity on the accuracy of forehand top spin of advanced players - Sadeghian Shahi, M. R.; Rahavi Ezabadi, R.; Abootalebi, N.; Moshiri, P. (Proceedings Book of The 15th ITTF Sports Science Congress Düsseldorf, 27th - 28th May 2017, 2017)
The purpose of this study was to determine the effects of the motivational and instructional self-talk and task complexity on the accuracy of forehand top spin of table tennis in advanced players. The 30 male advanced (28±10.6 years old) were divided into 3 groups (2 experimental and 1 control). The task complexity was determined by color of ball and impact place. In other words, sequence sending of the ball were changed after two balls and this trend continued. The keywords for motivational selftalk was "I can do" and " I correctly recognize", and for Instructional self-talk "pay attention" and "Close your paddle". Masters and et.al test (2008) was used to measure the accuracy of forehand topspin. After the pre-test, subjects took part in 6 training sessions including 20 trails per session. After 48 hours, they participated in post-test. The data were analyzed by paired-samples t-test, one way ANOVA and Bonferroni post hoc test. Results showed that there is a significant difference between the instructional and motivational self-talk in terms of task complexity. These findings suggested that instructional self-talk is the effective variable in performance of tasks that needs high complex decisions and accuracy.